The strategies of drug supply for patients with chronic hepatitis C - E. V. Kornilova; A. D. Ermolaeva; M. G. Rusanova; D. A. Andreev; M. V. Davydovskaya; T. N. Ermolaeva; A. g Pokatilo; K. I. Polyakova; V. A. Dubovtseva; K. А. Kokushkin; A. V. Devyatkin (Фармакоэкономика)
The report reviews the options of drug supply for patients with chronic hepatitis C in the Russian Federation and elsewhere. The results of the Moscow regional program aimed at improving the quality of medical care in such patients are discussed. The proposed measures contribute to the reduced mortality rate in patients suffering from infections. The prospects of further improvements in the availability of antiviral medications for patients with chronic viral hepatitis C are outlined.